POPULAR ECONOMY AND SOCIAL ORGANIZATION - Arguedas Abarca, María Fernanda (2020)
In the central theme, cases of social organization are developed to face economies in different periods, circumstances and places: Costa Rica, Argentina, Mexico and Spain.